Heading for the Future After COVID-19: Reflections and Recommendations on Teaching Processes in a Rapidly Changing Learning Landscape - Wanda Reyes-Velázquez; Carmen Pacheco-Sepúlveda (Central States Communication Association, 2022)
The COVID-19 pandemic posed numerous challenges for instructors and students. Professors, for example, struggled to quickly and effectively migrate face-to-face courses to remote teaching modalities. What had not been anticipated, however, were the additional challenges to be managed when returning to face-to-face and in-person teaching. This reflective essay provides some insight into how faculty at the University of Puerto Rico attempted to modify teaching practices to re-engage disengaged students as they returned to the campus classroom. Also, recommendations about how to move forward by applying a pedagogy of renewal are made.